The Clinical Significance of the Primary Malignant Melanoma of the Lower Respiratory Tract and/or Lung Based on the Analysis of Published Case Reports and of Two Patients. Issue 3 (1995) - Barzó, P.; Minik, K.; Tuka, P.; Kiss, J. I.
Abstract : Considering the data and including two patients of the authors, there exist only 18 authentic cases of primary malignant melanoma of the lower respiratory tract and/or the lung. The tumor was localized in the endobronchial space in 7 cases and only once in the trachea. Endobronchial localization, together with the involvement of the surrounding lung tissue, was found in two cases, whereas in 8 patients, the tumor was found exclusively in the lung parenchyma. Successful resection could be performed in 14 of the 18 cases. Survival was influenced primarily by operability, and on actual size and extension. The authors question the role of the obduction in the diagnostic criteria, because most of the survivors, even up to ten years postsurgery were considered primary. Apart from the various imaging methods, diagnostic endoscopy (i.e., bronchoscopy) and the histology of the biopsy material are major aides in the diagnosis of primary character, location, and operability, as well as in the elaboration of the surgical plans, than it is usual in cases of other tumors.